Bahaya Perundungan (Bullying) dan Pencegahannya Pada Siswa Sekolah Menengah Atas Katolik (SMAK) Negeri di Kabupaten Keerom - Asmarani, Nur; Girsang, Hotlarisda; Simanjuntak, Ayub Jose Luhut Parulian; Mambaya, Marthinus; Kaplele, Farida; Reumi, Frans; Marlissa, Elsyan R.; Pelupessy, Eddy; Palenewen, James Yoseph (Yayasan Daarul Huda Kruengmane, 2025)
Community service entitled The Dangers of Bullying and Its Prevention was carried out on students of State Catholic Senior High Schools (SMAK) in Keerom Regency on Friday, June 14, 2024. This activity was carried out because students still did not understand the dangers of Bullying and its Prevention. The methods used were lectures and discussions. The output of this community service is an understanding of the importance of preventive measures against bullying. Therefore, it is hoped that every student can avoid bullying, both physically, non-physically and through social media. Because these actions may have been carried out by students and may even have experienced bullying, but they are not aware of it, as well as the forms of bullying. The output of this community service activity is an increase in students' knowledge of the forms of bullying and their prevention, so that students can better understand and avoid bullying.